Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In Kassel's book on Quantum Groups, I am stuck on the following computation:

\begin{eqnarray*} [\Delta (E), \Delta (F)] &=& \Delta (E)\Delta (F)-\Delta (F)\Delta (E)\\ &=& (1\otimes E + E \otimes K) (K^{-1} \otimes F + F\otimes 1)\\ &&-(K^{-1}\otimes F+F\otimes 1)(1\otimes E+E\otimes K)\\ &=& K^{-1}\otimes EF + F\otimes E + EK^{-1}\otimes KF + EF\otimes K\\ &&-K^{-1}\otimes FE - K^{-1}E\otimes FK - F\otimes E - FE\otimes K\\ &=& K^{-1} \otimes (EF-FE) + (EF-FE) \otimes K\\ &=& K^{-1}\otimes [E,F] + [E,F]\otimes K\\ &=& \frac{K^{-1}\otimes (K-K^{-1})+(K-K^{-1})\otimes K}{q-q^{-1}}\\ &=& \frac{K\otimes K-K^{-1}\otimes K^{-1}}{q-q^{-1}}\\ &=& \frac{\Delta (K)-\Delta (K^{-1})}{q-q^{-1}} \end{eqnarray*}

The above computation was attempted by me, but I am not sure of one part, namely why is $EK^{-1}\otimes KF = -(K^{-1}E\otimes FK )$.

I understand that $E,F,K$ are variables that generate the quantum group $U_q(\mathfrak{sl}(2))$.

Sincere thanks for any help.

share|improve this question
add comment

1 Answer 1

up vote 3 down vote accepted

You have a sign error we have $EK^{-1}\otimes KF=K^{-1}E\otimes FK$. This is because of the following two relations: \begin{align*} KEK^{-1}&=q^2E\\ KFK^{-1}&=q^{-2}F \end{align*} Hence we have \begin{align*} EK^{-1}=q^2K^{-1}E\\ KF=q^{-2}FK \end{align*} This gives the above equality (since $q^2q^{-2}=1$ and you can put scalars in front of the tensor product).

Otherwise your computation is correct.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.